COMPARISON OF ABILITY PO4 AND NH3 DECREASE IN HOSPITAL WASTEWATER USING PHYTOREMEDIATION BATCH WITH EICHHORNIA CRASSIPES AND AZOLLA PINATA - AM Lelie Novia W; Wahyu Wilopo; Agus Prasetya (Master in Systems Engineering, 2020)
Hospital operations have the potential to produce waste, especially wastewater, which can cause environmental pollution. Therefore it is necessary to control the disposal of liquid waste that is discharged into the environment. It is required to reduce the pollution of wastewater management is excellent and appropriate legislation. Research methodology starts from the data observed laboratory test results for samples of hospital wastewater. From these data, it is known that the levels of phosphate and ammonia still do not meet quality standards following the Decree of the Minister of Environment No. 58 of 1995 regarding effluent standards for hospitals. Further research is limited only focused on decreased levels of phosphate and ammonia in hospital wastewater.Data research includes a phosphate concentration of outlets as a pilot study. The subsequent wastewater will be divided into seven-bath, three-bath containing wastewater and water hyacinth plants with a density different in each basin ie density of 60 mg/cm2, 90 mg/cm2, and 120 mg/cm2, three baths containing hospital wastewater and Azolla plant density of each tub 60 mg/cm2, 90 mg/cm2, 120 mg/cm2, and the control tanks containing wastewater without a given crop. Based on the results obtained, phosphate levels can meet the fastest quality standards for four days on a tub of hospital wastewater and water hyacinth with a density of 120 mg/cm2 and all of a tub of wastewater hospitals and Azolla. For ammonia takes the fastest four days, this happens in a tub filled with water hospital waste, and water hyacinth with a density of 120 mg/cm2 and the entire tub of wastewater hospitals and Azolla.